2022
DOI: 10.1107/s1600576722004265
|View full text |Cite
|
Sign up to set email alerts
|

Insights into a dual-phase steel microstructure using EBSD and image-processing-based workflow

Abstract: Quantitative metallography to understand the morphology of different crystallographic phases in a material often rests on the segmentation and classification of electron backscatter diffraction (EBSD) maps. Image analysis offers rich toolboxes to perform such tasks based on `scalar' images. Embracing the entire wealth of information provided by crystallography, operations such as erosion, dilation, interpolation, smoothing and segmentation require generalizations to do justice to the very nature of crystal ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The duplex microstructure was found to display a significantly higher content of close KS-OR interfaces, which are represented with white and yellow interfaces in Figure 3. However, no unique and strict orientation relationship exist between both phases, as already mentioned in previous work (Mollens, 2022b). Moreover, close to some primary ferrite boundaries, the austenite phase exhibit no longer a lath-like morphology and no OR is observed.…”
Section: Crystallographic and Morphological Features Of The Microstru...mentioning
confidence: 54%
See 3 more Smart Citations
“…The duplex microstructure was found to display a significantly higher content of close KS-OR interfaces, which are represented with white and yellow interfaces in Figure 3. However, no unique and strict orientation relationship exist between both phases, as already mentioned in previous work (Mollens, 2022b). Moreover, close to some primary ferrite boundaries, the austenite phase exhibit no longer a lath-like morphology and no OR is observed.…”
Section: Crystallographic and Morphological Features Of The Microstru...mentioning
confidence: 54%
“…Inside such a packet, the 4 variants belong 2 by 2 to two Bain domains. Finally, from the analysis of the experimental EBSD data (Mollens et al 2022b), four physical scales can be identified to describe the complex microstructure of the as received cast duplex steel. Figure 5 reports the microstructure with four identified physical scales from EBSD analysis, and the schematic principle of the three-scale homogenization model based on two scale transitions assuming that macro-homogeneity conditions are satisfied.…”
Section: Crystallographic and Morphological Features Of The Microstru...mentioning
confidence: 99%
See 2 more Smart Citations
“…The accurate identification of these microstructures for phase fraction calculation is crucial for evaluating the quality of Advanced High-Strength Steels (AHSS). Conventional methodologies like SEM analysis and Electron Backscatter Diffraction (EBSD) are commonly utilized for steel structure analysis, yet they are time-consuming, labor-intensive, and financially draining for extensive analysis [12,13], highlighting the necessity for alternative more efficient microstructure characterization methods. In this paper, we introduce a segmentation model for phase fraction calculation using a Deep Neural Network (DNN) on images of AHSS-a futuristic automotive steel material with tensile strengths surpassing 1 gigapascal (GPa).…”
Section: Introductionmentioning
confidence: 99%